Serum Amyloid A Promotes E-Selectin Expression via Toll-Like Receptor 2 in Human Aortic Endothelial Cells. (5th October 2016) - Nishida, Eisaku; Aino, Makoto; Kobayashi, Shu-ichiro; Okada, Kosuke; Ohno, Tasuku; Kikuchi, Takeshi; Hayashi, Jun-ichiro; Yamamoto, Genta; Hasegawa, Yoshiaki; Mitani, Akio
Abstract : Periodontitis is a chronic inflammatory disease that affects the periodontium. Recent studies suggest an association between periodontal and cardiovascular diseases. However, the detailed molecular mechanism is unknown. A previous study has demonstrated that experimental periodontitis induces serum amyloid A (SAA) in the liver and peripheral blood of ApoE-deficient mice as an atherosclerosis model. SAA is an acute-phase protein that affects systemic inflammation. The aim of this study is to investigate the atherosclerosis-onset mechanism using human aortic endothelial cells (HAECs) stimulated by SAA in vitro . Atherosclerosis PCR array and qPCR analyses showed upregulation of adhesion molecules such as intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and E-selectin in HAECs upon SAA stimulation. In addition, the results demonstrated that Toll-like receptor, TLR2, could serve as an important receptor of SAA in HAECs. Furthermore, small interfering RNA (siRNA) against TLR2 inhibited the upregulation of adhesion molecules in HAECs stimulated by SAA. Our results suggest that SAA stimulates the expression of adhesion molecules via TLR2. SAA could be an important molecule for atherosclerosis induced by periodontal disease.